2022
DOI: 10.1111/jam.15740
|View full text |Cite
|
Sign up to set email alerts
|

The intestinal microbiome associated with lipid metabolism and obesity in humans and animals

Abstract: Intestinal microbiota is considered to play an integral role in maintaining health of host by modulating several physiological functions including nutrition, metabolism and immunity. Accumulated data from human and animal studies indicate that intestinal microbes can affect lipid metabolism in host through various direct and indirect biological mechanisms. These mechanisms include the production of various signalling molecules by the intestinal microbiome, which exert a strong effect on lipid metabolism, bile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 127 publications
(155 reference statements)
0
8
0
Order By: Relevance
“…Moreover, hyperlipidemia–induced dysbiosis can lead to disorder of the local immune system, accompanied by production of inflammatory cytokines such as IL–1β, IL–6, and tumor necrosis factor (TNF)–α, and adipokines such as leptin in addition to increasing the intestinal permeability [ 28 ]. Furthermore, it affects the microglia in the brain through “gut–brain axis” leading to neuroinflammation, which in time affects the satiety centers, decreasing the anorexia hormones and producing more craving for food intake and excess body weight [ 29 ]. Additionally, the metabolites of gut microbiota act as a signaling pathway in lipid homeostasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hyperlipidemia–induced dysbiosis can lead to disorder of the local immune system, accompanied by production of inflammatory cytokines such as IL–1β, IL–6, and tumor necrosis factor (TNF)–α, and adipokines such as leptin in addition to increasing the intestinal permeability [ 28 ]. Furthermore, it affects the microglia in the brain through “gut–brain axis” leading to neuroinflammation, which in time affects the satiety centers, decreasing the anorexia hormones and producing more craving for food intake and excess body weight [ 29 ]. Additionally, the metabolites of gut microbiota act as a signaling pathway in lipid homeostasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary lipids majorly include triglycerides with smaller quantities of phospholipids, sphingolipids, cholesterol, and lipid‐soluble vitamins (Iqbal & Hussain, 2009 ; Jian et al., 2022 ). Lipids are majorly assimilated in the small intestine with the aid of liver‐derived bile salts.…”
Section: Macronutrient Metabolism By the Gut Microbiota And The Livermentioning
confidence: 99%
“…Dysbiosis can promote the translocation of bacterial products such as LPS, which are also known as endotoxins into the liver, leading to inflammation and the development of FLD. Studies have shown that the gut microbiome plays a crucial role in regulating hepatic lipid metabolism [ 140 ]. Dysbiosis during viral infections can lead to impaired lipid metabolism, promoting fat accumulation in the liver [ 141 ].…”
Section: Role Of Host Microbiota In Susceptibility To Viral Infection...mentioning
confidence: 99%